Analysis of Consumer Perception about Product Attributes Influencing the Decision to Buy of Solid Brem Madiun Outlets - Mustaniroh, Siti Asmaul; Astuti, Retno; Widyaningtyas, Dinar (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The research was made to analyze any attributes that influence the decision of buying of solid brem in Madiun town outlets. All attributes that might have been considered in buying decision of solid brem was listed by interviewing its consumers. The most popular brand was eventually used as a product reference. The perceived quality was then determined upon the consumersâ€™ selection on the listed attributes. The respondents were consumers at the outlets in Madiun town, the centre of solid brem produced in Java. The number of respondents, i.e. 80, was determined based on a linear time function. The data collected was then analyzed by means of the Cochran Q Test. Finally, an assessment was made on the performance of attributes of two other brands of solid brem in comparison with the product reference. Amongst the 13 attributes listed influencing consumers in buying of solid brem, only nine of them were considered to be important, namely: the brand, packaging material, ability of packaging material protecting the quality of product, brem colour, expire date, taste, halal warrants, sales (outlets) location and availability of product. Whilst the packaging shape, packaging colour, brem composition and cleanliness were not considered as the important ones. The results indicated that the brand, expired date, and taste were considered to be the prominent attributes. It was obvious that the product reference of solid brem was rated better in these three attributes than the other two competitors. Â Key words: consumer perception, product attribute, solid brem